PREDIKSI PELUANG KEMATIAN DAN KELAHIRAN MURNI PENDUDUK KABUPATEN MERAUKE MENGGUNAKAN METODE BIRTH AND DEATH PROCESS - Riyana, Minuk; Welliken K., Marius Agustinus (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2021)
This study aims to estimate the probability of birth and death purely based on gender and population data of Merauke City. The chance of birth and death will be used to estimate the life table of the elderly in a population of the City of Merauke. The method used in this research is the birth and process method. The Birth and death process method which is a Poisson distribution is used to predict the chances of birth and death at time t. If the birth and death process fulfills the linearity requirements, then the processes are called the Yule-Furry process. This research discusses the stochastic process of pure birth-death with two sexes in the Yule-Furry Process. From the data on the population of Merauke district which is divided based on the sex of men and women using the pure birth and death model, the calculation results show that the probability value at the time interval 0 â‰¤ t <1 hour, at the initial time t = 0, the chance of individual birth at female sex is stationary at a value of 0.1762, while the chance of individual death for female sex is stationary at a value of 0.00154. The odds of birth and death in male individuals are stationary at a value of 0.305034 and 0, 059487.